Estudio de prefactibilidad para la instalación de una planta de producción de masa de galleta comestible a base de harina de trigo (Triticum aestivum) - Mujica Torpoco, Luciana Alexandra (2021)
The production facility for edible biscuit dough made of wheat flour will be located in the department of Lima. The demanding of the project for the last evaluated year is 157 194 containers and each one will be sold at a selling price of S / 14,5. The production process for the final product consists of pasteurizing the flour, mixing it with the chocolate chips, packaging and labeling. In addition, the plant will have 655m2 considering both areas administrative and production. The total investment to execute the project is S / 514 249, an amount that will be financed 70% by a bank and the remaining 30% by own capital. The economic flow of the project reflects an Internal Rate of Return (IRR) of 47% and a payback period of 2,47 years.